Application of photocatalytic proxone process for petrochemical wastewater treatment - Mehrab Aghazadeh; Amir Hessam Hassani; Mehdi Borghei (Scientific Reports, 2023)
Abstract Industrial wastewaters are different from sanitary wastewaters, and treatment complications due to their unique characteristics, so biological processes are typically disrupted. High chemical oxygen demand, dye, heavy metals, toxic organic and non-biodegradable compounds present in petroleum industry wastewater. This study intends to optimize the photocatalytic proxone process, utilizing a synthesized ZnO–Fe3O4 nanocatalyst, for petroleum wastewater treatment. The synthesis of ZnO–Fe3O4 was done by air oxidation and layer-by-layer self-assembly method and XRD, SEM, EDAX, FT-IR, BET, DRS, and VSM techniques were used to characterize the catalyst. Central composite design (CCD) method applied to investigated the effect of pH (4–8), reaction time (30–60 min), ozone gas concentration (1–2 mg/L-min), hydrogen peroxide concentration (2–3 mL/L) and the amount of catalyst (1–0.5 g/L) on the process. In the optimal conditions, biological oxygen demand (BOD5) and total petroleum hydrocarbon (TPH) removal, reaction kinetic, and synergistic effect mechanisms on the process were studied. Based on the ANOVA, a quadratic model with R2 = 0.99, P-Value = 0.0001, and F-Value = 906.87 was proposed to model the process. Based on the model pH = 5.7, ozone concentration = 1.8 mg/L-min, hydrogen peroxide concentration = 2.5 mL/L, reaction time = 56 min, and the catalyst dose = 0.7 g/L were proposed as the optimum condition. According to the model prediction, an efficiency of 85.3% was predicted for the removal of COD. To evaluate the accuracy of the prediction, an experiment was carried out in optimal conditions, and experimentally, a 52% removal efficiency was obtained. Also, at the optimum condition, BOD5 and TPH removal were 91.1% and 89.7% respectively. The reaction kinetic follows the pseudo-first-order kinetic model (R2 = 0.98). Also, the results showed that there is a synergistic effect in this process. As an advanced hybrid oxidation process, the photocatalytic proxone process has the capacity to treat petroleum wastewater to an acceptable standard.